Treatment of textile wastewater using sequential sulfate-reducing anaerobic and sulfide-oxidizing aerobic membrane bioreactors - Yurtsever, Adem; Cinar, Ozer; Sahinkaya, Erkan (ELSEVIER SCIENCE BV, 2016)
This study aims at evaluating the performance of sequential sulfate-reducing anaerobic and sulfide oxidizing aerobic membrane bioreactors (MBRs) for the treatment of synthetic textile wastewater. The process performance was evaluated under varying concentrations of COD (1000-2000 mg/L), NaCl (500-1000 mg/L), and sulfate (500-1500 mg/L), but keeping dye (Remazol Brilliant Violet 5R) concentration constant at 200 mg/L. In sulfate reducing anaerobic MBR (AnMBR), COD removal efficiency remained between 80% and 85%. The sulfate reduction efficiency was directly related with COD/sulfate ratio. Almost complete decolorization was attained in the AnMBR, whereas slight recolorization was observed in the AeMBR due to autooxidation of aromatic amines. EDS analyses illustrated that cake layer in AnMBR contained much higher amounts of S, Fe and Cu due to formation of metal sulfide precipitates, whereas Ca and P were the major inorganic elements in AeMBR. In the cake layers of both MBRs, high molecular weight soluble organics were observed by gel permeation chromatographic analyses together with the identification of proteins and polysaccharides by the FT-IR analyses. Capillary suction time, specific resistance to filtration and supernatant filterability tests illustrated that AnMBR sludge had less filterability and stable operation was possible with a flux of around 5 LMH. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Anaerobic membrane bioreactor; Sulfate reduction; Textile wastewater; Color removal; Membrane fouling; EXTRACELLULAR POLYMERIC SUBSTANCES; FLUIDIZED-BED REACTOR; BAFFLED REACTOR; PILOT-SCALE; AZO-DYE; RETENTION TIME; CRITICAL FLUX; PERFORMANCE; DECOLORIZATION; PERSPECTIVES; Engineering; Polymer Science